Digital Modern Financial Systems In The Perspective of Cyber Risk Management : A Structural Equation Modelling Approach - Lisnawaty, Lisnawaty; Mujanah, Siti; Fianto, Achmad Yanu Alif (Universitas Trunojoyo Madura, 2025)
The rapid digitalization of financial systems has amplified exposure to cyber risks, posing substantial threats to institutional performance and systemic stability. This study investigates how Cyber Risk Management (CRM) strengthens Financial System Resilience (FSR), both directly and indirectly, through Regulatory Compliance (RC) and Technological Safeguards (TS). Using Structural Equation Modelling (SEM) with simulated survey data (n = 200), the findings reveal that CRM has a strong direct effect on FSR (β = 0.41, p 0.001) and significant indirect effects via RC (β = 0.07, 95% CI [0.02–0.12]) and TS (β = 0.14, 95% CI [0.08–0.20]). The overall model demonstrates robust explanatory power (R² = 0.65), confirming that 65% of financial system resilience is explained by CRM, RC, and TS. These results validate a multi-layered framework in which governance, compliance, and technology jointly enhance systemic resilience. The study contributes theoretically by integrating cyber risk management with resilience theory, and practically by offering a model for policymakers and financial institutions to design more adaptive, secure, and technology-driven financial ecosystems in the digital era.